THE IMPACT OF STRAWBERRY GENERATION LABELING ON SELF-RESILIENCE AND INTERGENERATIONAL COMMUNICATION - Rizky Jagad Dito Pratisco; Ahmad Subekti (KAIS Kajian Ilmu Sosial, 2026)
This study investigates the impact of the "Strawberry Generation" label on self-resilience and intergenerational communication among young adults. Employing a qualitative methodology with an interpretative phenomenological design, the research emphasizes participants’ subjective experiences in receiving, interpreting, and responding to social labels. Data were collected through in-depth interviews with ten participants aged 21–28, comprising university students, employees, and recent graduates. Thematic analysis was conducted through repeated transcript review, coding meaningful statements, clustering codes into themes, and interpreting these themes using social labelling theory, self-fulfilling prophecy, self-efficacy, Family Communication Patterns Theory, and Communication Accommodation Theory. Findings indicate that the Strawberry Generation label does not represent an objective generational category but rather a social construction arising from family comments, social media, peer interactions, and workplace contexts. The label can undermine self-confidence within unsupportive power relations however, it can be mitigated through open family communication, self-efficacy, and communicative accommodation in professional settings. Theoretically, the study extends interpersonal communication research by demonstrating that generational labelling shapes self-identity through everyday communication processes rather than exclusively through individual psychological assessment. Practically, it underscores the importance of supportive family communication, intergenerational mentoring, and workplace dialogue to prevent youth from being reduced to stereotypes of fragility.